Convergence between the dimensional PD models of ICD-11 and DSM-5: a meta-analytic approach - Hualparuca-Olivera, Luis; Caycho-Rodríguez, Tomás; Torales, Julio; Ramos-Campos, Dayana (Frontiers in Psychiatry, 2023)
In the current diagnostic systems, ICD-11 and DSM-5, the diagnosis of personality disorder (PD) aim at dimensional examination of the severity of its dysfunction and the stylistic features that accompany it. Since their implementation, or even before, several measures have been developed to assess PD severity and traits in both models. Thus, convergent validity metrics have been reported with various PD measures; however, the convergence of the same constructs included in the measures of these two models remains undefined. The objective of the present review was to examine whether there is a sufficient relationship between PD measures of the ICD-11 and DSM-5 AMPD in the general population. For this meta-analytic review, systematic searches were conducted in Web of Science, PubMed, Scopus, and Google Scholar. We included studies that reported Pearson’s r correlations without restrictions on language, age, sex, setting, type of sample, or informant of the measures. We examined the quality of the evidence with the JBI CACACSS, and performed the random effects meta-analysis with the ‘meta’ package of the RStudio software. Of the 5629 results returned by the search, 19 studies were eligible; and showed moderate quality. 13 studies provided two or more correlations resulting in a total of 59 studies for meta-analysis. The overall effect size estimate (correlation) was moderate for the overall model (r = 0.61, 95% CI [0.56, 0.67], p < 0.0001, I2 = 97.9%). The convergent validity between measures of PD severity and traits between one diagnostic system and another has been demonstrated.